Ecology in action - Singer, Fred (New Delhi : Cambridge University Press, 2025)
"This undergraduate textbook enables students to develop a strong grasp of key ecological concepts, a deep understanding of the origins and evolution of scientific knowledge, and an appreciation of their realworld applications. The pedagogically-rich and engaging second edition is filled with diverse resources that support active learning"--
Includes bibliographical references and index.
Keywords: Ecology -- Research. -- Organisnmal ecology; Ecology -- Case studies. -- Ecosystem and global ecology